Monitoring of three-phase distribution power transformer based on the Internet of Things (IoT) and SCADA - Yusnan Badruzzaman; Revi Alvin Razaqi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The three-phase distribution transfomer, equipment for stepping down the voltage from medium (20/11,5 kV) to low voltage network (400/231 V) with a constant power, is a type of the PT. PLN (Persero) assets which has a direct relationship with customers. The condition and the performance of transformer are affecting on how the continuity of the electricity distributed. Hence, the monitoring process of three-phase distribution transfomer condition and performance should be done. Some elements which have to be monitored such as voltage (ZMPT101B sensor), current (ACS712 30 A sensor), power, and transfomer load. Those elements could be included as an electrical indicator.And then the transfomer’s temperature (DS18B20 sensor) and the oil transfomer level (HC SR04 sensor) could be included as a mechanical indicator. All of the sensors are processed and programmed with Arduino Mega 2560 which has been connected directly into an additional modul called Ethernet shield and router. The results then emitted by WiFi into SCADA to be shown. The results shown by SCADA is the information whether transformer need to be maintened or not